Raw materials for in-situ generation of core-shell structure ceramic core and preparation method
By adding nano-alumina powder and fused corundum powder to the raw materials of the ceramic core, a core-shell structure is generated in situ, which solves the problem of poor performance of the ceramic core at high temperatures and significantly improves the high-temperature bending strength of the ceramic core. and creep resistance.
Patent Information
- Application Number
- CN202411907360.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-01-24
AI Technical Summary
The existing ceramic cores have poor performance at high temperatures and are prone to deformation or fracture, which affects the manufacturing of blades. In the existing fiber reinforcement methods, the fiber bonding strength between the matrix is insufficient, which affects the performance strengthening of the ceramic core.
By adding nano-alumina powder and fused corundum powder to the ceramic core raw material, a core-shell structure with alumina as the core and mullite fiber as the shell is generated in situ, thereby improving the bonding strength between the fiber and the matrix.
It significantly enhances the high -temperature anti -bending strength and high temperature resistance of ceramic core, improves the comprehensive performance of the core, and solves the problem of fibrous decentralization and insufficient binding strength.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic powder metallurgy, and in particular to a raw material for in-situ generating a core-shell structure ceramic core and a preparation method thereof. Background Art
[0002] The performance of aircraft engines is the main factor restricting the development of the aviation industry. The thrust-to-weight ratio that affects the key performance of aircraft engines is closely related to the temperature bearing capacity of the hot end component, the turbine blades. At present, improving the temperature bearing capacity of turbine blades through the hollow air-cooled structure of turbine blades has become an important means to improve engine performance. The ceramic core is the key to realizing the hollow inner cavity structure of engine blades. With the development of cooling technology, the inner cavity structure of blades has become increasingly complex, which puts higher requirements on the structure and performance of ceramic cores.
[0003] At present, the most widely used ceramic core is a silicon oxide-based ceramic core, which uses quartz glass as the main raw material, has excellent high-temperature physical and chemical stability, and has excellent removability. However, as the requirements for blade air cooling efficiency become higher and higher, the more complex the inner cavity structure is, the higher the structural complexity requirements for the ceramic core are, and higher requirements are inevitably placed on the performance of the ceramic core to meet practical applications. For example, the smallest part of a certain type of ceramic core is only millimeter in size, which often affects the overall manufacturing of the blade due to the poor high-temperature performance of the core, that is, deformation or fracture at high temperatures. This not only increases the manufacturing cost, but also greatly reduces the success rate of the product.
[0004] As mentioned above, the performance of the silicon oxide ceramic core prepared only with quartz glass powder as raw material can no longer meet the manufacturing requirements of high-efficiency air-cooled blades. Therefore, it has become an important means to enhance the silicon oxide-based ceramic core by adding mineralizers. Particles such as zirconium silicate, zirconium oxide, aluminum oxide, silicon carbide, and silicon nitride have achieved improvements in the performance of oxide ceramic cores, but the improvement is still limited. Fiber reinforcement can utilize its overseas association effect formed in three-dimensional space and make full use of the void structure inside the ceramic core to achieve the enhancement effect on the performance of the silicon oxide ceramic core. For example, some aluminum oxide fibers are introduced into the ceramic core to enhance its performance and play a reinforcing role (such as patent CN112358309A). Fully utilizing the reinforcement effect of the fiber can further enhance the performance of the ceramic core to meet higher requirements. However, the fiber is usually introduced by direct addition, which will inevitably lead to problems such as entanglement or breakage of the fiber during the mixing process, affecting the dispersion of the fiber in the ceramic matrix and reducing the effect of the fiber-reinforced ceramic core. At present, there are also studies on strengthening ceramic cores by in-situ generated fibers. However, the bonding strength between these fibers and the matrix is not enough, and they cannot effectively play a blocking role when the ceramic core is subjected to force. The performance enhancement effect is not good. New strategies are needed to improve the bonding strength between the fibers and the matrix to achieve their strengthening effect on the ceramic core.
[0005] The existing patent CN112358309A discloses a method for preparing an alumina fiber reinforced ceramic core, in which alumina ceramic fibers are used to reinforce the ceramic core, a new fiber adding method is selected with a solvent as a carrier, different contents of alumina fibers are added to the ceramic core, and the fibers are dispersed by mechanical stirring and a hydroxypropyl methylcellulose dispersant to prepare an alumina fiber reinforced ceramic core.
[0006] The existing patent CN113354422A discloses a ceramic core for single crystal high temperature alloy blades and a preparation method thereof. The raw materials of the ceramic core include: quartz glass powder 55%-75%, fused corundum powder 5%-15%, zirconium silicate powder 5%-15%, yttrium oxide 0.5%-5%, lanthanum oxide 0.5%-5% and plasticizer 10%-25%. The above raw materials are mixed, heated, stirred, cooled, molded, and finally calcined and strengthened to form the ceramic core.
[0007] In summary, the above two existing patents have not completely solved the problem that the high temperature performance of the ceramic core needs to be further improved. Therefore, the development of a ceramic core with excellent comprehensive performance, especially excellent high temperature performance, is of great significance to the development of the aviation industry. Summary of the invention
[0008] Based on the above technical problems, the present invention proposes a raw material and preparation method for in-situ generated core-shell structure ceramic core, which solves the problem that the bonding strength between in-situ generated fibers and the matrix is insufficient and has limited effect on strengthening the performance of the ceramic core in the prior art.
[0009] To achieve the above purpose, the present invention proposes a raw material and preparation method for in-situ generation of a core-shell structure ceramic core. The specific technical solution is as follows:
[0010] A raw material for in-situ generation of a core-shell structure ceramic core comprises refractory powder and a mineralizer, and further comprises fused corundum powder and nano-alumina powder, wherein the mineralizer is zirconium silicate powder, the weight percentage of the refractory powder in the ceramic core raw material is 70%-85%, the weight percentage of the zirconium silicate powder in the ceramic core raw material is 5%-20%, the weight percentage of the fused corundum powder in the ceramic core raw material is 5%-10%, and the weight percentage of the nano-alumina powder in the ceramic core raw material is 1%-5%; the refractory powder is quartz glass powder.
[0011] Furthermore, the weight percentage of the refractory material powder in the ceramic core raw material is 73%-80%, the weight percentage of the zirconium silicate powder in the ceramic core raw material is 10%-15%, the weight percentage of the fused corundum powder in the ceramic core raw material is 6%-9%, and the weight percentage of the nano alumina powder in the ceramic core raw material is 2%-4%.
[0012] Furthermore, the powder particle size range of the refractory material powder is 1-60μm and the powder purity is not less than 99.95%, the powder particle size range of the zirconium silicate powder is 1-40μm and the purity is not less than 98.6%, the powder particle size range of the fused corundum powder is 1-30μm and the purity is not less than 99.9%, and the powder particle size range of the nano alumina powder is 10-300nm and the purity is not less than 99.9%.
[0013] The present invention also provides a method for preparing an in-situ generated core-shell structure ceramic core, using the raw materials for the in-situ generated core-shell structure ceramic core to prepare a ceramic core, the preparation method specifically comprising the following steps:
[0014] S1, mixing ceramic core raw materials to form ceramic core slurry;
[0015] S2, using ceramic core slurry to prepare a ceramic core blank;
[0016] S3, the ceramic core blank is sintered by powder embedding to form a ceramic core.
[0017] Furthermore, in step S1, the ceramic core raw material is added to the dispersant in batches, and uniform mixing is achieved through vacuum stirring to form a ceramic core slurry.
[0018] Further, in step S1, quartz glass powder, zirconium silicate powder, fused corundum powder and nano alumina powder are weighed in proportion, placed in a vacuum dryer for drying and then mixed evenly to form a ceramic core raw material, and the ceramic core raw material is added to liquid paraffin in batches and evenly mixed;
[0019] The drying temperature of the vacuum dryer is 100-150°C, and the drying time is 12-24h;
[0020] The melting temperature of the paraffin wax is 80-95°C, the speed of the vacuum stirring is 12-180 r / min, the stirring time is 5-10h, and the vacuum degree is 4×10 -2 -6×10 -2 Pa.
[0021] Further, in step S2, the ceramic core slurry is added into a core pressing machine, and a ceramic core blank is obtained by a hot pressing injection molding method;
[0022] The molding pressure of the core pressing machine is 5-10MPa.
[0023] Furthermore, in step S3, the ceramic core blank is buried with powder and then sintered at high temperature to form a ceramic core;
[0024] The final sintering temperature of the high-temperature sintering is 1000-1300°C, and the heating process of the high-temperature sintering includes multiple stages. The heating range of each stage is 150-300°C, the heating rate of each stage is 2-10°C / min, and the insulation time after heating in each stage is 4-15h.
[0025] Furthermore, the multiple stages include: the first stage: room temperature to 200°C, the heating rate is 2°C / min, and the temperature is kept at 200°C for 4 hours; the second stage: 200°C to 400°C, the heating rate is 3°C / min, and the temperature is kept at 400°C for 5 hours; the third stage: 400°C to 600°C, the heating rate is 5°C / min, and the temperature is kept at 600°C for 8 hours; the fourth stage: 600°C to 900°C, the heating rate is 8°C / min, and the temperature is kept at 900°C for 10 hours; the fifth stage: 900°C to a maximum of 1200°C, the heating rate is 10°C / min, and the temperature is kept for 12 hours.
[0026] Based on the above technical solution, compared with the prior art, the present invention has at least the following beneficial effects:
[0027] 1. The present invention proposes a raw material and a preparation method for in-situ generating a core-shell structure ceramic core. During the high-temperature sintering process, a core-shell structure with alumina as the core and mullite fiber as the shell is in-situ generated, which solves the dispersion of the fiber, strengthens the bonding strength between the fiber and the raw material particles, realizes the effective blocking effect on cracks when the ceramic core is subjected to force, and further enhances the performance of the oxide ceramic core.
[0028] 2. The present invention proposes a raw material and preparation method for in-situ generation of a core-shell structure ceramic core. By adding nano-alumina powder and fused corundum powder to refractory powder, the in-situ generation of a core-shell structure with alumina as the core and mullite fiber as the shell is achieved. Mullite is a high-temperature stable phase, and its pinning effect at high temperature can enhance the high-temperature strength of the ceramic core.
[0029] 3. The present invention proposes a raw material and a preparation method for in-situ generating a core-shell structure ceramic core, which has a simple preparation process, good fiber dispersion, high fiber-matrix bonding strength, and excellent performance enhancement effect on the ceramic core.
[0030] 4. The present invention proposes a raw material and preparation method for in-situ generation of a core-shell structure ceramic core, which is also applicable to the design and development of ceramic cores of other systems and has important promotion value. DETAILED DESCRIPTION
[0031] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0032] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.
[0033] In order to solve the problem in the prior art that the bonding strength between in-situ generated fibers and a matrix is insufficient and has a limited effect on strengthening the performance of ceramic cores, the present invention provides a raw material and a preparation method for in-situ generated core-shell structure ceramic cores.
[0034] To achieve the above objectives, the present invention proposes a raw material and a preparation method for in-situ generating a core-shell structure ceramic core. By introducing nano-alumina powder and fused corundum powder, a core-shell structure with alumina as the core and mullite fiber as the shell is generated in situ, thereby enhancing the performance of the ceramic core.
[0035] The raw material for in-situ generation of a core-shell structure ceramic core proposed by the present invention includes, in addition to refractory powder and a mineralizer, nano-alumina powder and fused corundum powder, and the mineralizer is zirconium silicate powder. The weight percentage of the refractory powder in the ceramic core raw material is 70%-85%, the weight percentage of the zirconium silicate powder in the ceramic core raw material is 5%-20%, the weight percentage of the fused corundum powder in the ceramic core raw material is 5%-10%, and the weight percentage of the nano-alumina powder in the ceramic core raw material is 1%-5%.
[0036] Among them, quartz glass powder is used as refractory powder, the powder size range of refractory powder is 1-60μm, and the powder purity is ≥99.95%. The chemical composition of zirconium silicate powder includes 64-67% ZrO2 and 33-36% SiO2, the powder size range of zirconium silicate is 1-40μm, and the powder purity is ≥98.6%, the powder size range of fused corundum is 1-30μm, and the powder purity is ≥99.9%, and the powder size range of nano alumina is 10-300nm, and the powder purity is ≥99.9%.
[0037] The method for preparing a ceramic core using the ceramic core raw material specifically includes:
[0038] S1, mixing ceramic core raw materials to form ceramic core slurry;
[0039] Specifically, refractory powder, zirconium silicate powder, fused corundum powder and nano alumina powder are weighed according to weight percentage, placed in a vacuum dryer for drying, and then uniformly mixed to form a ceramic core raw material; then the ceramic core raw material is added to the paraffin melted into liquid, and the powder and the paraffin are uniformly mixed by vacuum stirring to form a ceramic core slurry. The weight percentage of the paraffin in the ceramic core slurry is 10-20%.
[0040] Among them, the drying time of the vacuum dryer is 12-24 h, and the drying temperature is 100-150°C.
[0041] The melting temperature of paraffin is 80-95°C, the vacuum stirring speed is 12-180r / min, and the vacuum degree is 5×10 -2 -6×10 -2 Pa, vacuum stirring time is 5-10h.
[0042] S2, forming a ceramic core blank using the ceramic core slurry;
[0043] Specifically, the ceramic core slurry obtained in step S1 is added into a core pressing machine, and a ceramic core blank is obtained by hot pressing injection molding.
[0044] Among them, the molding pressure of the core pressing machine is 5-10MPa.
[0045] S3, burying the ceramic core blank with powder and sintering to obtain a ceramic core.
[0046] Specifically, after the ceramic core blank is embedded with powder, it is sintered at high temperature to form a ceramic core with a core-shell structure reinforcement.
[0047] Among them, the final sintering temperature of high-temperature sintering is 1000-1300°C, and the heating process of high-temperature sintering includes multiple stages. The heating range of each stage is 150-300°C, the heating rate of each stage is 2-10°C / min, and the insulation time after heating in each stage is 4-15h.
[0048] The preparation method of the in-situ generated core-shell structure ceramic core is described below by using specific data values.
[0049] Example 1
[0050] S1. Quartz glass powder with an average particle size of 20 μm and a purity of ≥99.95%, zirconium silicate powder with an average particle size of 15 μm and a purity of ≥98.6%, fused corundum powder with an average particle size of 20 μm and a purity of ≥99.9%, and nano alumina powder with an average particle size of 50 nm and a purity of ≥99.9% were weighed in weight percentages of 70%, 20%, 5% and 5% respectively, and placed in a vacuum dryer for 12 hours at a drying temperature of 120° C., and then evenly mixed to form a ceramic core raw material;
[0051] Weigh paraffin wax according to 16% of the total weight of the ceramic core slurry, place it in a vacuum mixer to melt, add the dried ceramic core raw materials to the melted paraffin wax in batches, and use vacuum stirring to achieve uniform dispersion of the powder in the paraffin wax to form a ceramic core slurry. The melting temperature of the paraffin wax is 90°C, and the vacuum degree of the vacuum mixer is 5×10 -2 Pa, stirring time is 8h.
[0052] S2, placing the ceramic core slurry into a core pressing machine, using a mold to press the green blank, the molding pressure is 5MPa, and a ceramic core green blank is obtained;
[0053] S3. Fill the ceramic core blank with alumina filler and then sinter it. According to the first stage, the temperature is from room temperature to 200°C, the heating rate is 2°C / min, and it is kept at 200°C for 4 hours; the second stage is from 200°C to 400°C, the heating rate is 2°C / min, and it is kept at 400°C for 5 hours; the third stage is from 400°C to 600°C, the heating rate is 3°C / min, and it is kept at 600°C for 8 hours; the fourth stage is from 600°C to 900°C, the heating rate is 5°C / min, and it is kept at 900°C for 10 hours; the fifth stage is from 900°C to a maximum of 1200°C, the heating rate is 10°C / min, and it is kept at 10 hours; finally, the ceramic core is obtained after cooling to room temperature with the furnace.
[0054] The flexural strength of the ceramic core prepared in this embodiment is 20.9 MPa at room temperature, 16.4 MPa at 1550° C., and 1.17 mm at 1550° C.
[0055] Example 2
[0056] S1. Quartz glass powder with an average particle size of 20 μm and a purity of ≥99.95%, zirconium silicate powder with an average particle size of 15 μm and a purity of ≥98.6%, fused corundum powder with an average particle size of 20 μm and a purity of ≥99.9%, and nano alumina powder with an average particle size of 50 nm and a purity of ≥99.9% were weighed in weight percentages of 73%, 15%, 10% and 2% respectively, and dried in a vacuum dryer for 12 hours at a drying temperature of 120° C., and then uniformly mixed to form a ceramic core raw material;
[0057] Weigh paraffin wax according to 20% of the total weight of the ceramic core slurry, place it in a vacuum mixer to melt, add the dried ceramic core raw materials to the melted paraffin wax in batches, and use vacuum stirring to achieve uniform dispersion of the powder in the paraffin wax to form a ceramic core slurry. The melting temperature of the paraffin wax is 95°C, and the vacuum degree of the vacuum mixer is 4×10 -2 Pa, stirring time is 10 h.
[0058] S2, placing the ceramic core slurry into a core pressing machine, using a mold to press the green blank, the molding pressure is 6MPa, and a ceramic core green blank is obtained;
[0059] S3. Fill the ceramic core blank with alumina filler and then sinter it. According to the first stage, the temperature is from room temperature to 200°C, the heating rate is 3°C / min, and it is kept at 200°C for 4 hours; the second stage is from 200°C to 450°C, the heating rate is 3°C / min, and it is kept at 450°C for 5 hours; the third stage is from 450°C to 700°C, the heating rate is 3°C / min, and it is kept at 700°C for 5 hours; the fourth stage is from 700°C to 1000°C, the heating rate is 5°C / min, and it is kept at 1000°C for 8 hours; finally, the temperature is increased from 1000°C to 1300°C, the heating rate is 10°C / min, and it is kept at 10 hours; finally, the ceramic core is obtained after cooling to room temperature with the furnace.
[0060] The flexural strength of the ceramic core prepared in this embodiment is 21.5 MPa at room temperature, 17.9 MPa at 1550° C., and 1.28 mm at 1550° C.
[0061] Example 3
[0062] S1. Quartz glass powder with an average particle size of 20 μm and a purity of ≥99.95%, zirconium silicate powder with an average particle size of 15 μm and a purity of ≥98.6%, fused corundum powder with an average particle size of 20 μm and a purity of ≥99.9%, and nano alumina powder with an average particle size of 50 nm and a purity of ≥99.9% were weighed in weight percentages of 78%, 12%, 7% and 3% respectively, and placed in a vacuum dryer for 12 hours at a drying temperature of 120° C., and then evenly mixed to form a ceramic core raw material;
[0063] Weigh paraffin wax at 14% of the total weight of the ceramic core slurry and place it in a vacuum mixer to melt. Add the dried ceramic core raw materials to the melted paraffin wax in batches, and use vacuum stirring to achieve uniform dispersion of the powder in the paraffin wax to form a ceramic core slurry. The melting temperature of the paraffin wax is 90°C, and the vacuum degree of the vacuum mixer is 4.5×10 -2 Pa, stirring time is 7 h.
[0064] S2, placing the ceramic core slurry into a core pressing machine, using a mold to press the green blank, the molding pressure is 8MPa, and a ceramic core green blank is obtained;
[0065] S3. Use alumina filler to fill the ceramic core blank and then sinter it. The first stage is from room temperature to 200℃, the heating rate is 2℃ / min, and it is kept at 200℃ for 4 hours; the second stage is from 200℃ to 400℃, the heating rate is 3℃ / min, and it is kept at 400℃ for 5 hours; the third stage is from 400℃ to 600℃, the heating rate is 5℃ / min, and it is kept at 600℃ for 8 hours; the fourth stage is from 600℃ to 900℃, the heating rate is 8℃ / min, and it is kept at 900℃ for 10 hours; the fifth stage is from 900℃ to a maximum of 1200℃, the heating rate is 10℃ / min, and it is kept at 12 hours; finally, the ceramic core is obtained after cooling to room temperature with the furnace.
[0066] The flexural strength of the ceramic core prepared in this embodiment is 22.5 MPa at room temperature, 19.4 MPa at 1550° C., and 1.01 mm at 1550° C.
[0067] Example 4
[0068] S1. Quartz glass powder with an average particle size of 20 μm and a purity of ≥99.95%, zirconium silicate powder with an average particle size of 15 μm and a purity of ≥98.6%, fused corundum powder with an average particle size of 20 μm and a purity of ≥99.9%, and nano alumina powder with an average particle size of 50 nm and a purity of ≥99.9% were weighed in percentages of 80%, 10%, 6% and 4% by weight, respectively, and dried in a vacuum dryer for 12 hours at a drying temperature of 120° C., and then uniformly mixed to form a ceramic core raw material;
[0069] Weigh paraffin wax according to 16.5% of the total weight of the ceramic core slurry and place it in a vacuum mixer to melt. Add the dried ceramic core raw materials to the melted paraffin wax in batches, and use vacuum stirring to achieve uniform dispersion of the powder in the paraffin wax to form a ceramic core slurry. The melting temperature of the paraffin wax is 85°C, and the vacuum degree of the vacuum mixer is 5.5×10 -2 Pa, stirring time is 9h.
[0070] S2, take out the ceramic core slurry and place it in a core pressing machine, use a mold to press the blank, the molding pressure is 8MPa, and obtain a ceramic core blank;
[0071] S3. Use alumina filler to fill the ceramic core blank and then sinter it. According to the first stage, the temperature is from room temperature to 150℃, the heating rate is 3℃ / min, and it is kept at 150℃ for 4 hours; the second stage is from 150℃ to 300℃, the heating rate is 3℃ / min, and it is kept at 300℃ for 5 hours; the third stage is from 300℃ to 500℃, the heating rate is 5℃ / min, and it is kept at 500℃ for 8 hours; the fourth stage is from 500℃ to 800℃, the heating rate is 5℃ / min, and it is kept at 800℃ for 810 hours; finally, the temperature is increased from 800℃ to 1100℃, the heating rate is 10℃ / min, and it is kept at 15 hours; finally, the ceramic core is obtained after cooling to room temperature with the furnace.
[0072] The flexural strength of the ceramic core prepared in this embodiment is 21.8 MPa at room temperature, 17.4 MPa at 1550° C., and 1.14 mm at 1550° C.
[0073] Example 5
[0074] S1. Quartz glass powder with an average particle size of 20 μm and a purity of ≥99.95%, zirconium silicate powder with an average particle size of 15 μm and a purity of ≥98.6%, fused corundum powder with an average particle size of 20 μm and a purity of ≥99.9%, and nano alumina powder with an average particle size of 50 nm and a purity of ≥99.9% were weighed in weight percentages of 85%, 5%, 9% and 1% respectively, and dried in a vacuum dryer for 12 hours at a drying temperature of 120° C., and then uniformly mixed to form a ceramic core raw material;
[0075] Weigh paraffin wax according to 17.5% of the total weight of the ceramic core slurry and place it in a vacuum mixer to melt. Add the dried ceramic core raw materials to the melted paraffin wax in batches, and use vacuum stirring to achieve uniform dispersion of the powder in the paraffin wax to form a ceramic core slurry. The melting temperature of the paraffin wax is 90°C, and the vacuum degree of the vacuum mixer is 5×10 -2 Pa, stirring time is 8 h.
[0076] S2, take out the ceramic core slurry and place it in a core pressing machine, use a mold to press the blank, the molding pressure is 10MPa, and obtain a ceramic core blank;
[0077] S3. Fill the ceramic core blank with alumina filler and then sinter it. According to the first stage, the temperature is from room temperature to 200℃, the heating rate is 3℃ / min, and it is kept at 200℃ for 4h; the second stage is from 200℃ to 400℃, the heating rate is 3℃ / min, and it is kept at 400℃ for 6h; the third stage is from 400℃ to 600℃, the heating rate is 3℃ / min, and it is kept at 600℃ for 8h; the fourth stage is from 600℃ to 900℃, the heating rate is 5℃ / min, and it is kept at 900℃ for 10h; finally, the temperature is increased from 900℃ to 1250℃, the heating rate is 10℃ / min, and it is kept at 10h; finally, the ceramic core is obtained after cooling to room temperature with the furnace.
[0078] The ceramic core prepared in this embodiment has a flexural strength of 19.4 MPa at room temperature, a flexural strength of 1550° C. of 15.8 MPa, and a deflection of 1550° C. of 1.11 mm.
[0079] Comparative Example
[0080] S1. Quartz glass powder with an average particle size of 20 μm and a purity of ≥99.95% and zirconium silicate powder with an average particle size of 15 μm and a purity of ≥98.6% are weighed in 80% and 20% weight percentages respectively, and dried in a vacuum dryer for 12 hours at a drying temperature of 120° C., and then uniformly mixed to form a ceramic core raw material;
[0081] Weigh paraffin wax at 16% of the total weight of the ceramic core slurry and place it in a vacuum mixer to melt. Add the dried ceramic core raw materials to the melted paraffin wax in batches, and evenly disperse the powder in the paraffin wax through vacuum stirring to form a ceramic core slurry. The melting temperature of the paraffin wax is 90°C, and the vacuum degree of the vacuum mixer is 5×10 -2 Pa, stirring time is 8h.
[0082] S2, taking out the ceramic core slurry and placing it in a core pressing machine, and using a mold to press the green blank to obtain a ceramic core green blank;
[0083] S3. Use alumina filler to fill the ceramic core blank and then sinter it. According to the first stage, the temperature is from room temperature to 200℃, the heating rate is 3℃ / min, and it is kept at 200℃ for 4h; the second stage is from 200℃ to 400℃, the heating rate is 3℃ / min, and it is kept at 400℃ for 5h; the third stage is from 400℃ to 600℃, the heating rate is 3℃ / min, and it is kept at 600℃ for 8h; the fourth stage is from 600℃ to 900℃, the heating rate is 5℃ / min, and it is kept at 900℃ for 8h; finally, the temperature is increased from 900℃ to 1200℃, the heating rate is 10℃ / min, and it is kept at 10h; finally, the ceramic core is obtained after cooling to room temperature with the furnace.
[0084] The ceramic core prepared in this embodiment has a flexural strength of 15.3 MPa at room temperature, a flexural strength of 10.19 MPa at 1550° C., and a deflection of 1.69 mm at 1550° C.
[0085] Compared with the results of the comparative examples, the room temperature flexural strength, high temperature flexural strength and high temperature creep resistance of the silicon-based ceramic core prepared according to the method of the present invention are greater than the results in the comparative examples, and the performance of the ceramic core is significantly improved.
[0086] It can be seen that the core-shell structure with alumina as the core and mullite fiber as the shell generated in situ inside the silicon oxide ceramic core provided by the present invention significantly enhances the room temperature and high temperature bending strength and high temperature creep resistance of the oxide ceramic core, and improves the comprehensive performance of the core. At the same time, the present invention can be applied to the development and application of ceramic cores of other systems.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
[0088] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0089] It should be noted that, in the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
Claims
1. A raw material for in-situ generation of a core-shell structure ceramic core, comprising refractory powder and a mineralizer, characterized in that: It also includes fused corundum powder and nano alumina powder, the mineralizer is zirconium silicate powder, the weight percentage of the refractory material powder in the ceramic core raw material is 70%-85%, the weight percentage of the zirconium silicate powder in the ceramic core raw material is 5%-20%, the weight percentage of the fused corundum powder in the ceramic core raw material is 5%-10%, and the weight percentage of the nano alumina powder in the ceramic core raw material is 1%-5%; the refractory material powder is quartz glass powder.
2. The raw material for in-situ generation of core-shell structure ceramic core according to claim 1, characterized in that: The weight percentage of the refractory material powder in the ceramic core raw material is 73%-80%, the weight percentage of the zirconium silicate powder in the ceramic core raw material is 10%-15%, the weight percentage of the fused corundum powder in the ceramic core raw material is 6%-9%, and the weight percentage of the nano alumina powder in the ceramic core raw material is 2%-4%.
3. The raw material for in-situ generation of core-shell structure ceramic core according to claim 1, characterized in that: The powder particle size range of the refractory material powder is 1-60μm and the powder purity is not less than 99.95%, the powder particle size range of the zirconium silicate powder is 1-40μm and the purity is not less than 98.6%, the powder particle size range of the fused corundum powder is 1-30μm and the purity is not less than 99.9%, and the powder particle size range of the nano alumina powder is 10-300nm and the purity is not less than 99.9%.
4. A method for preparing an in-situ generated core-shell structure ceramic core, using the raw material for the in-situ generated core-shell structure ceramic core as claimed in any one of claims 1 to 3 to prepare the ceramic core, characterized in that: The preparation method specifically comprises the following steps: S1, mixing ceramic core raw materials to form ceramic core slurry; S2, using ceramic core slurry to prepare a ceramic core blank; S3, the ceramic core blank is sintered by powder embedding to form a ceramic core.
5. The method for preparing an in-situ generated core-shell structure ceramic core according to claim 4, characterized in that: In step S1, ceramic core raw materials are added to the dispersant in batches, and uniform mixing is achieved through vacuum stirring to form ceramic core slurry.
6. The method for preparing an in-situ generated core-shell structure ceramic core according to claim 5, characterized in that: In step S1, quartz glass powder, mineralizer, fused corundum powder and nano alumina powder are weighed in proportion, placed in a vacuum dryer for drying and then mixed evenly to form a ceramic core raw material, and the ceramic core raw material is added to liquid paraffin in batches and evenly mixed; The drying temperature of the vacuum dryer is 100-150°C, and the drying time is 12-24h; The melting temperature of the paraffin wax is 80-95°C, the speed of the vacuum stirring is 12-180 r / min, the stirring time is 5-10h, and the vacuum degree is 4×10 -2 -6×10 -2 Pa.
7. The method for preparing an in-situ generated core-shell structure ceramic core according to claim 4, characterized in that: In step S2, the ceramic core slurry is added into a core pressing machine, and a ceramic core blank is obtained by a hot pressing injection molding method; The molding pressure of the core pressing machine is 5-10MPa.
8. The method for preparing an in-situ generated core-shell structure ceramic core according to claim 4, characterized in that: In step S3, the ceramic core blank is buried with powder and then sintered at high temperature to form a ceramic core; The final sintering temperature of the high-temperature sintering is 1000-1300°C, and the heating process of the high-temperature sintering includes multiple stages. The heating range of each stage is 150-300°C, the heating rate of each stage is 2-10°C / min, and the insulation time after heating in each stage is 4-15h.
9. The method for preparing an in-situ generated core-shell structure ceramic core according to claim 8, characterized in that: The multiple stages include: the first stage: room temperature to 200°C, the heating rate is 2°C / min, and the temperature is kept at 200°C for 4 hours; the second stage: 200°C to 400°C, the heating rate is 3°C / min, and the temperature is kept at 400°C for 5 hours; the third stage: 400°C to 600°C, the heating rate is 5°C / min, and the temperature is kept at 600°C for 8 hours; the fourth stage: 600°C to 900°C, the heating rate is 8°C / min, and the temperature is kept at 900°C for 10 hours; the fifth stage: 900°C to a maximum of 1200°C, the heating rate is 10°C / min, and the temperature is kept for 12 hours.
Citation Information
Patent Citations
Preparation method of alumina fiber reinforced ceramic core
CN112358309A
Ceramic core for single-crystal high-temperature alloy blade and preparation method of ceramic core
CN113354422A
Manufacturing method of alumina-based ceramic core for precision casting of turbine blade of gas turbine
CN110483087A
Inorganic fiber composite silicon-based ceramic mold core and preparation method thereof
CN110590387A
Preparation method of mullite whisker reinforced aluminum-based ceramic core for directional solidification
CN112047726A
Cited By
Anti-permeation burnt-on sand coating for steel casting and preparation process of anti-permeation burnt-on sand coating
CN120243826A
Preparation method of aluminum-based ceramic core
CN122254871A